The Effect Of Self-Efficacy On Employee Performance With Employee Engagement As An Intervening Variable - Rini Juni Astuti; Arsyadu Rohmah Arraniry (Jurnal Ekonomi, 2024)
This study was aimed to determine the effect of self-efficacy on employee performance through employee engagement as a mediator for the teachers of the Bina Anak Sholeh School in Yogyakarta, Indonesia. This research was quantitative research using primary data obtained by distributing questionnaires with google form. The sampling technique used in this study was a non-probability sampling technique/saturated sampling, carried out by all teachers at the Bina Anak Sholeh School in Yogyakarta Province. This study was carried out with a total of 106 respondents. This study derives hypotheses by processing data through the SPSS version 26 program. The results of this study indicate that self-efficacy has a positive and significant effect on employee performance, self-efficacy has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on performance employees, and employee engagement mediates self-efficacy on employee performance.